Diagnóstico na Secretaria Estadual de Transportes do Pará: um pressuposto para aplicação da gestão documental - MORAES, Maira Moreira Pampolha (2017)
The purpose of this research was to present a situational diagnosis in Secretaria de Estado de Transporte do Pará as presuppotion for Records Management application, from this Diagnosis on presenting the documentary flow in SETRAN‘S activities, verifying accumulated documentary mass situation; identifying problems related to archival activities and how a archivist is necessary based on the Law nº 6.546/1978. It is characterized as empirical research using case study method with a qualitative approach. The theoretical composition was formed by readings related to the Public Administration and its functionalities, national policies of information access. Archival Science and Records Management including its phases and clarifying about Diagnosis Concept and the archivist‘s performance in this process. This research expose a data survey made by a Diagnosis that was made by interview and photograph. The research‘s results indicates the characteristics of the company, records management‘s procedures that are made and the collection‘s characteristics, analyzing the best way of Records Management application and proposing suggestions of improvement for SETRAN‘s accumulated documentary mass, including to justify the archivist presence in that organization.